NUMERIC MODELING TO SIMULATE THE SOIL WATER INFILTRATION PROCESS - PREVEDELLO, Celso Luiz; LOYOLA, Jocely Maria Thomazoni; COSTABILE, Marcos dos Santos; HORODENSKI, José (Scientia Agraria, 2002)
Several laboratorial tests were carried out with the objective to evaluate the statistical hypothesis of the equalities between observated and simulated values from a numerical model of the soil water infiltration process. This model was created Richards equation linearized in space and by Newton-Raphson iterative process to solve this unlinearized equation on time. The results showed that model was reliable to evaluate the one-dimensional soil water infiltration process for both homogeneous and heterogeneous porous media.